2016
DOI: 10.1111/hepr.12716
|View full text |Cite
|
Sign up to set email alerts
|

Close correlation between urinary sodium excretion and response to tolvaptan in liver cirrhosis patients with ascites

Abstract: Aim: To assess the correlation between response to tolvaptan and treatment-related factors in liver cirrhosis patients.Methods: This single-center retrospective study was carried out at Shonan Kamakura General Hospital in Kanagawa, Japan, between October 2013 and September 2015. Forty-three liver cirrhosis patients (mean age, 65.7 years) with insufficient responses to conventional diuretics for at least 7 days were enrolled. All patients received oral tolvaptan (7.5 mg/day for 7 days) and guideline-directed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
3
25
1
Order By: Relevance
“…Urinary Na/K ratio has been reported to be an indicator of daily sodium excretion [29, 30] and an indirect indicator of mineral corticoid activity [31, 32]. In agreement with a previous study [18], the present study showed that spot urinary sodium may be predictive of response to tolvaptan. Urinary sodium can be evaluated easily and reproducibly.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Urinary Na/K ratio has been reported to be an indicator of daily sodium excretion [29, 30] and an indirect indicator of mineral corticoid activity [31, 32]. In agreement with a previous study [18], the present study showed that spot urinary sodium may be predictive of response to tolvaptan. Urinary sodium can be evaluated easily and reproducibly.…”
Section: Discussionsupporting
confidence: 91%
“…Serum creatinine levels at 4, 8, and 12 weeks (±1 week at each point) after tolvaptan administration were obtained. Patients showing a ≥–2 kg reduction in body weight within 1 week of tolvaptan administration were defined as responders, with other patients were defined as non-responders [18]. The median observation period was 124 days (range 4–1,058 days).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Free water clearance [14], aquaporin-2/AVP [15], and urinary Na excretion [16] were reported to be predictors of a tolvaptan response in patients with cirrhosis. The combination of BUN/Cr and urine Na/K ratios was the first reported predictor of a tolvaptan response.…”
mentioning
confidence: 99%